Age‐related deep white matter changes in myelin and water content: A T2 relaxometry study. Issue 5 (12th March 2019) - Papadaki, Efrosini; Kavroulakis, Eleftherios; Kalaitzakis, Georgios; Karageorgou, Dimitra; Makrakis, Dimitrios; Maris, Thomas G.; Simos, Panagiotis G.
Abstract : Background: According to the retrogenesis hypothesis, the rate of age‐related changes in white matter (WM) myelin content varies between early myelinating (parietal, occipital) and late myelinating (prefrontal, lateral–posterior temporal) areas. The multiecho spin echo (MESE), PD‐to‐T2 ‐weighted sequence provides an index of myelin content (myelin water fraction [MWF]) derived from measurements of myelin water (via the short T2 component [10–50 msec]) and intra‐ and extracellular water (via the long T2 component [>50–200 msec]). Purpose: To assess the shape and regional variations in the rate of age‐related myelin and water content changes in deep WM regions using the MESE sequence. Study Type: Prospective, cross‐sectional. Population: In all, 90 healthy adults aged 22–81 years. Field Strength/Sequence: 1.5T/ T1 w, T2 w, fluid attenuated inversion recovery (FLAIR), MESE sequences. Assessment: Short T2, long T2, and MWF values were measured in prefrontal, parietal, lateral–posterior temporal, and occipital normal‐appearing WM (NAWM) areas. Statistical Tests: Linear and quadratic effects of age on long T2 and MWF were assessed through regression analyses. Regional variations in the effect of age on long T2 and MWF values at both the individual and group level were examined, using regression and analysis of covariance (ANCOVA) analyses, respectively, controlling for total WM volume. Results: The rate of age‐related changes in long T2 and MWF was higher for older persons and a significant increase or decline, respectively, was first noted at 60–69 years ( P  < 0.0033). MWF values peaked earlier (at 30 years of age) and displayed a steeper age‐related reduction in prefrontal and lateral–posterior temporal NAWM as compared with the occipital lobes ( P  < 0.05). The opposite pattern of age‐related effect was found for long T2 values. Data Conclusion: Significant age‐related reductions in myelin content were closely followed by corresponding increases in intra‐ and extracellular water content. These changes were more pronounced among elderly people and followed an anterior–posterior pattern. Level of Evidence: 2 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2019;50:1393–1404.